2013
DOI: 10.4103/0971-4065.111861
|View full text |Cite
|
Sign up to set email alerts
|

Syndrome of rapid-onset end-stage renal disease in two consecutive renal transplant recipients

Abstract: A syndrome of rapid-onset end-stage renal disease (SORO-ESRD) following acute kidney injury (AKI) in native kidneys was described recently. To what extent this syndrome of unanticipated and rapidly irreversible ESRD impacts renal allograft survival is unknown. Over 6 months, we managed two deceased donor renal transplant recipients (RTRs) with rapid acceleration of previously stable allograft chronic kidney disease to abruptly terminate in irreversible ESRD following AKI. These are the first reports of SORO-ES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 7 publications
(11 reference statements)
1
13
0
Order By: Relevance
“…Rapid decline in kidney function to ESRD was considered to have occurred if a patient was documented to have estimated GFR >30 mL/min/1.73 m 2 within 3 months prior to the initiation of chronic dialysis . Incidentally, we must observe here that their definition very closely mirrored our standard definition of SORO‐ESRD . Lee et al revealed that 8 of 105 incident chronic dialysis patients in one dialysis unit (7.6%; 95% confidence interval [CI] 3.4%–14.5%) and 9 of 71 incident patients at another dialysis unit (12.7%, 95% CI 6.0%–22.7%), suffered rapid yet permanent decline in kidney function consistent with SORO‐ESRD …”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…Rapid decline in kidney function to ESRD was considered to have occurred if a patient was documented to have estimated GFR >30 mL/min/1.73 m 2 within 3 months prior to the initiation of chronic dialysis . Incidentally, we must observe here that their definition very closely mirrored our standard definition of SORO‐ESRD . Lee et al revealed that 8 of 105 incident chronic dialysis patients in one dialysis unit (7.6%; 95% confidence interval [CI] 3.4%–14.5%) and 9 of 71 incident patients at another dialysis unit (12.7%, 95% CI 6.0%–22.7%), suffered rapid yet permanent decline in kidney function consistent with SORO‐ESRD …”
Section: Introductionmentioning
confidence: 84%
“…In 2010, we first described the syndrome of rapid onset end‐stage renal disease (SORO‐ESRD), from the Renal Unit of Mayo Clinic Health System, Eau Claire, in Northwestern Wisconsin, USA, in the journal, Renal Failure . This syndrome represents acute precipitate yet irreversible renal failure following acute kidney injury (AKI) in contradistinction to “classic” end‐stage renal disease (ESRD) where CKD to ESRD progression is progressive, linear, time‐dependent, and predictable over years to sometimes decades, going through penultimate CKD stages to inexorably end in ESRD, requiring permanent renal replacement therapy in the form of dialysis and/or renal transplantation . Remarkably, “classic” ESRD is typified by patients with CKD who demonstrate often predictably increasing serum creatinine levels and, therefore, simultaneously falling estimated GFR levels, associated increasing proteinuria where applicable and ultimately leading inexorably to terminal symptomatic ESRD and the need for permanent renal replacement therapy (RRT) …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…concluded that acute kidney injury on top of CKD may be the reason for a suboptimal dialysis start in over 30% of CKD patients with established nephrologist care . Onuigbo have extensively reviewed this phenomenon, which they have termed the syndrome of rapid‐onset end‐stage renal disease (SORO‐ESRD), and in a large‐scale review of acute kidney injury studies in the literature, they noted SORO‐ESRD rates ranging from 1% to 85% . With incident HD catheter access around 71% in the United States even in patients with predialysis nephrology care, we suggest that the unpredictable and often accelerating rate of decline in eGFR plays a role in this poor outcome.…”
Section: Discussionmentioning
confidence: 99%